Manhaj Tafsir Integratif: Formulasi Kerangka Epistemologis bagi Pengembangan Ilmu Tafsir - Muhammad Fikran Said; Achmad Abubakar; Muhammad Irham (Jurnal Ilmu Agama Indonesia, 2026)
The development of Qur'anic exegesis in the contemporary era faces increasingly complex challenges arising from social transformation, scientific advancement, technological innovation, and cultural diversity. Conventional interpretive approaches, which often rely on a single methodological perspective, are considered insufficient to provide comprehensive and contextual interpretations of the Qur'an in addressing modern societal issues. This study aims to formulate an Integrative Tafsir Methodology (Manhaj Tafsir Integratif) as an epistemological framework for the development of Qur'anic exegesis by integrating the normative authority of revelation with contemporary scientific approaches. This research employed a qualitative approach using a library research design. Data were collected through documentary studies of the Qur'an, Hadith, classical tafsir literature, academic books, and scholarly journal articles related to Islamic epistemology, Qur'anic interpretation, and knowledge integration. The data were analyzed using content analysis combined with conceptual analysis to identify, classify, and synthesize relevant concepts into a coherent epistemological framework. The findings reveal that the Integrative Tafsir Methodology is constructed upon four fundamental components, namely sources of knowledge, interpretive approaches, supporting scientific disciplines, and validation mechanisms for interpretation. The integration of bayānī, burhānī, and 'irfānī approaches with the social sciences, humanities, and natural sciences produces a more comprehensive, adaptive, and contextually relevant model of Qur'anic interpretation while maintaining the Qur'an's authority as the primary source of Islamic teachings. This study contributes theoretically to the development of the epistemology of Qur'anic exegesis and proposes a methodological framework that can serve as a reference for future tafsir studies in the contemporary academic context.